ANALISIS KORELASI PERILAKU BELAJAR DENGAN HASIL BELAJAR PESERTA DIDIK KELAS V SD DI KOTA SERANG - Subagio, Rohmad; Rahmat, Mamat; Ikrom, Fadhli Dzil (Journal of Professional Elementary Education, 2024)
Student behavior greatly influences the achievement of learning outcomes because learning is adding and acquiring a certain amount of knowledge. Learning outcomes are generally defined as the relationship between students and the systems around them during the schooling process, which leads to changes in behavior in the cognitive, affective and psychomotor fields, which are represented by symbols or numbers. The research conducted focused analysis on the relationship or correlation between learning behavior and learning outcomes of elementary school students in Serang City. The aim of this research is to analyze the relationship or correlation between learning behavior and learning outcomes of elementary school students in Serang City. Data collection techniques were obtained using learning behavior questionnaires and observing student learning outcomes. Sampling was carried out using simple random sampling techniques in three elementary schools in Serang City, totaling 90 students. The research results show that the average value of student learning outcomes is 83.60. Prerequisite testing, the normality test is carried out with a normal probability plot test which is quite effective in detecting whether a study has a normal distribution or not. Based on this test, the data is normally distributed because the points on the diagram always follow and approach the diagonal. The significance value of the learning behavior variable with the learning outcome variable is 0.000 where 0.000 < 0.05, so there is a correlation between the learning behavior variable and the student's learning outcomes. The test results show that there is a significant relationship or correlation between learning behavior variables and student learning outcomes